Genetic mapping of the LOSS OF PARTHENOGENESIS locus in Pilosella piloselloides and the evolution of apomixis in the Lactuceae - Bicknell, Ross; Gaillard, Marion; Catanach, Andrew; McGee, Robert; Erasmuson, Sylvia; Fulton, Beatrice; Winefield, Christopher (Frontiers in Plant Science, 2023)
Pilosella piloselloides var. praealta (syn. P. praealta; Hieracium praealtum) is a versatile model used to study gametophytic apomixis. In this system apomixis is controlled by three loci: one that controls the avoidance of meiosis (LOA), one that controls the avoidance of fertilization (LOP) and a third that controls autonomous endosperm formation (AutE). Using a unique polyhaploid mapping approach the LOP locus was mapped to a 654 kb genomic interval syntenic to linkage group 8 of Lactuca sativa. Polyhaploids form through the gametophytic action of a dominant determinant at LOP, so the mapped region represents both a functional and a physical domain for LOP in P. piloselloides. Allele sequence divergence (ASD) analysis of the PARTHENOGENESIS (PAR) gene within the LOP locus revealed that dominant PAR alleles in Pilosella remain highly similar across the genus, whilst the recessive alleles are more divergent. A previous report noted that dominant PAR alleles in both Pilosella and Taraxacum are modified by the presence of a class II transposable element (TE) in the promoter of the gene. This observation was confirmed and further extended to the related genus Hieracium. Sufficient differences were noted in the structure and location of the TE elements to conclude that TE insertional events had occurred independently in the three genera. Measures of allele crossover amongst the polyhaploids revealed that P. piloselloides is an autopolyploid species with tetrasomic inheritance. It was also noted that the dominant determinant of LOP in P. piloselloides could transmit via a diploid gamete (pollen or egg) but not via a haploid gamete. Using this information, a model is presented of how gametophytic apomixis may have evolved in several members of the Lactuceae, a tribe of the Asteraceae.